Analysis of Corporate Governance practices in the Colombia Stock Exchange (2019)
This paper discusses the application of corporate governance practices, as defined in the Code of Best Corporate Practices (Código País) in issuers Colombia Stock Exchange (BVC). Using regression models is evidence linking the implementation of corporate governance practices and the total amount demanded by investors in the market, this relationship is significant in non-financial issuers. It is observed that corporate governance practices related to board the greatest influence on demand, however, are applied to a lesser extent by issuers.